2018
DOI: 10.1093/nar/gky628
|View full text |Cite|
|
Sign up to set email alerts
|

Parentally inherited long non-coding RNA Cyrano is involved in zebrafish neurodevelopment

Abstract: Transfer of genetic material from parents to progeny via fusion of gametes is a way to ensure flow of information from one generation to the next. Apart from the genetic material, gametes provide a rich source of other factors such as RNA and proteins which can control traits of the embryo. Non-coding RNAs are not only carriers of regulatory information but can also encode memory of events of parental life. Here, we explore the possibility of parental inheritance of non-coding RNAs, especially long non-coding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…The mode of transportation of RNAs may be via membrane-bound vesicles that are expelled from cells and contain an abundance of small RNAs [15][16][17], including miRNAs [18]. Long non-coding RNAs have also been indirectly postulated to be transferred to offspring due to experience-dependent alterations in the sperm [19][20][21][22]. We, therefore, postulated that somatically expressed RNAs may be transported to the germline allowing real-time heritability of somatic, experience-dependent alterations.…”
Section: Introductionmentioning
confidence: 99%
“…The mode of transportation of RNAs may be via membrane-bound vesicles that are expelled from cells and contain an abundance of small RNAs [15][16][17], including miRNAs [18]. Long non-coding RNAs have also been indirectly postulated to be transferred to offspring due to experience-dependent alterations in the sperm [19][20][21][22]. We, therefore, postulated that somatically expressed RNAs may be transported to the germline allowing real-time heritability of somatic, experience-dependent alterations.…”
Section: Introductionmentioning
confidence: 99%
“…The third column shows the transcript ID for the investigated lncRNA or its genomic coordinate in GRCz10. Column Four represents the expression dynamics of the lncRNAs (see also Figure S3) (log2 (FPKM +1) between 0 and 8) 25 Cyrano cyrano is evolutionarily conserved lncRNA and based on morpholino studies, has been suggested to have essential functions during zebrafish embryogenesis 23 and brain morphogenesis 32 . cyrano has also been suggested to act as a sponge (decoy-factor) for HuR during neuronal proliferation 33 , regulate miR-7 mediated embryonic stem cell differentiation 34 , and control the level of miR-7 in the adult mouse brain 35 .…”
mentioning
confidence: 99%
“…The lncRNA OIP5-AS1 (known as Cyrano in zebrafish) is highly and ubiquitously expressed in various tissues and species 12 . 12 Cyrano has been shown to promoting zebrafish brain development, and silencing of Cyrano by miR-7 without changing zygotic Cyrano altered the brain architecture at 24 hours post fertilization and 48 hours post fertilization 13 . 13 In the lens, OIP5-AS1 is upregulated in the HLECs of patients with cataracts.…”
mentioning
confidence: 99%
“… 12 Cyrano has been shown to promoting zebrafish brain development, and silencing of Cyrano by miR-7 without changing zygotic Cyrano altered the brain architecture at 24 hours post fertilization and 48 hours post fertilization 13 . 13 In the lens, OIP5-AS1 is upregulated in the HLECs of patients with cataracts. 10 This molecule has been reported as a tumor suppressor or oncogene depending on the tumor type.…”
mentioning
confidence: 99%